Optimization of GERD Therapeutic Regimen Based on ANN and Realization of MATLAB - Wei-Wu Wang; Rui-Qing Ni; Fang-Yan Yu; Guo-Feng Lou; Cai-Dan Zhao (KeAi Communications Co., Ltd., 2018)
ABSTRACT: Objective To optimize therapeutic regimens for gastro-esophageal reflux disease (GERD), artificial neural networks (ANNs) are used to simulate and set up an intelligent traditional Chinese medicine (TCM) treatment system.Methods ANNs were employed for machine learning; the clinical syndrome differentiation and treatment determination were simulated through systematic learning of therapeutic regimens for GERD symptoms in the ancient literature; and case simulation was conducted to achieve objective verification.Results The conformity of machinery prescription with the ancient literature exceeded 95%.Conclusion The application of machine learning to TCM intelligent prescription is feasible and worthy of further study. Keywords: Artificial intelligence, TCM expert system, Gastro-esophageal reflux disease, Artificial neural network, MATLAB